Assessing Caregiver Burden in Caregivers of Patients with Schizophrenia and Bipolar Affective Disorder in Kathmandu Medical College - Sharma, Rachana; Sharma, Subhash Chandra; Pradhan, Sudarshan N (Journal of Nepal Health Research Council, 2018)
Background: Schizophrenia and bipolar affective disorder are chronic psychiatric illness that requires long term care. This study tends to measure psychological burden and factors associated with it among caregivers of these two illnesses. Methods: This is a cross- sectional study that included participants by purposive sampling method. Self designed performa was used to collect the socio-demographic details of the caregivers. Modified caregiver strain index was used to assess the overall stress. Beck`s depression inventory and Beck`s anxiety inventory was used to assess depression and anxiety respectively. Results: Hundred caregivers, 50 each of schizophrenia and bipolar affective disorder were enrolled. Seventy-two percent of caregivers were found to have higher level of stress. Twenty-five percent had depression and 29% anxiety related problems. Stress was found to be significantly associated with being in debt, longer duration of illness, education level, marital status, subjective feeling of psychological stress and self- acknowledgement of need of professional help. Caregivers of both group experienced similar level of stress. Conclusions: Psychological burden is seen to be high in caregivers of patients of Schizophrenia and Bipolar Affective Disorder.